Fabrication and Filtration Performance of Aquaporin Biomimetic Membranes for Water Treatment. Issue 3 (3rd July 2022) - Beratto-Ramos, Angelo; Dagnino-Leone, Jorge; Martínez-Oyanedel, José; Aranda, Mario; Bórquez, Rodrigo
ABSTRACT: Desalination is considered one of the strongest alternatives to face global water scarcity. Since conventional reverse osmosis is an energy-intensive process, Aquaporin biomimetic membranes (ABM) emerge as an effective alternative to increase productivity and reduce energy consumption. Despite the highly theoretical water permeability and selectivity of aquaporins (Aqps), in practice, ABM did not achieve the expected performance. This review is focused on each step of the ABM fabrication process in order to find critical points where efforts should be made for future studies. Fabrication procedures include Aqp production, reconstitution into vesicles, immobilization in porous substrates and filtration performance. The principal identified challenge is the need for implementing monitoring and optimization techniques. Also, new strategies for protein production, stabilization, reconstitution, and support affinity could offer significant breakthroughs for developing ABMs as a viable emerging technology.